Punching shear behaviour of steel fibre reinforced self-compacting concrete flat slabs - Zamri, Nor Fazlin (2021)
Steel fibre reinforced self-compacting concrete (SFRSCC) consolidates under its own weight and has been shown to have the ability in providing efficient reinforcement mechanism. The research was carried out by leveraging the benefits of the SFRSCC to solve the punching shear problem caused by multiaxial forces in disturbed regions in reinforced concrete (RC) flat slabs. This thesis presents the results of three experimental testing phases to investigate the effectiveness of the SFRSCC, self-compacting concrete (SCC) and the normal concrete (NC) in resisting punching shear in RC flat slabs. Shear reinforcement in the forms of vertical links and welded inclined bars were also investigated in the slabs cast with SCC. The effect of the thickness of the slab, and the limiting area of SFRSCC around the column were also examined. The fresh and hardened properties of these concretes, as well as the optimum content of fibre in the SFRSCC used in the flat slab specimens were determined from the tests in Phase 1. Tests to study on the biaxial behaviour of the concrete to simulate the multi-axial force effects in the RC flat slabs were carried out in Phase 2. Phase 3 deals with the structural testing of slab specimens, tested under a single point load in the middle until failure. The results showed that SFRSCC slabs can withstand higher punching shear load than NC and SCC slabs, with and without shear reinforcement. The failure mode of all fibrous specimens were found to be more ductile as compared to others. The results also revealed that slabs with SFRSCC within a square area around the column can be as efficient in resisting the punching shear as the ones with the SFRSCC cast over the entire slab. These findings were corroborated from biaxial behaviour of concrete in Phase 2. The incorporation of steel fibres into the concrete matrix provides confining pressure, which contributes to an increase in concrete strength under biaxial loading whilst ensuring ductile failure. In term of verification, the numerical analysis with two semi-empirical expressions, namely the strut-and-tie model and the additive model is also presented. The analysis results for the appropriate specimens show good agreement with experimental results, with the additive model giving the closest estimate of the punching shear capacity of the slabs.